2020
DOI: 10.21037/atm-20-2274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of metagenomic next-generation sequencing for active tuberculosis in clinical practice at a tertiary general hospital

et al.

Abstract: Background: To evaluate the diagnostic accuracy of metagenomic next-generation sequencing (mNGS) for active tuberculosis (TB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…High-quality data were obtained by removing low-quality bases, linker sequences, and short sequences (< 35 bp). The process of subtracting the human host sequence and aligning the remaining sequences were described in the previous study (Jin et al, 2020). The remaining data by removal of low-complexity reads were classified by simultaneously aligning to Pathogens metagenomics Database (PMDB).…”
Section: Bioinformatic Analysis and Criteria For Positive Resultsmentioning
confidence: 99%
“…High-quality data were obtained by removing low-quality bases, linker sequences, and short sequences (< 35 bp). The process of subtracting the human host sequence and aligning the remaining sequences were described in the previous study (Jin et al, 2020). The remaining data by removal of low-complexity reads were classified by simultaneously aligning to Pathogens metagenomics Database (PMDB).…”
Section: Bioinformatic Analysis and Criteria For Positive Resultsmentioning
confidence: 99%
“…For instance, Chen et al found that mNGS improved the diagnosis rate of Chlamydia psittaci through a retrospective analysis of nine cases of psittacosis pneumonia, 13 while Jin et al showed that the overall sensitivity of mNGS was superior to that of culture (49.6% vs 35.2%, respectively) in the diagnosis of 125 cases of active tuberculosis. 14 mNGS was also reported to improve the diagnosis rate of viral infections in plasma samples, and to identify dengue virus 1 and…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study has indicated that the diagnostic accuracy of mNGS in detecting active TB is higher than that of culture on liquid medium (the MGIT 960 system) (49.6% vs 35.2%). In addition, the turnaround time of mNGS detection, 32-36 hours, is markedly shorter than the 2-6 weeks required for the MGIT 960 system [14].…”
Section: Application Of Mngs In Detecting M Tuberculosismentioning
confidence: 99%